Women,Seduction, and Betrayal in Biblical Narrative - Bach,Alice (Cambridge University Press, 1997)
This accessible, readable book looks at the cultural study of the Bible, challenging the traditional mode of reading the women in the Bible. Alice Bach applies literary theory, cultural representations of biblical figures, films, and paintings to a close reading of a group of biblical texts revolving around the 'wicked' literary figures in the Bible. She compares the biblical character of the wife of Potiphar with the Second Temple Period narratives and rabbinic midrashim that expand her story. She then reads Bathsheba against a Yiddish novel by David Pinski, and finally looks at the Biblical Salome against a very different Salome created by Oscar Wilde, and the selection of Salomes created by Hollywood. Bach argues that biblical characters have a life in the mind of the reader independent of the stories in which they were created, thus making the reader the site at which the texts and the cultures that produced them come together.